The combined Zr and Hf isotope inventory of bulk rock and sequentially leached chondrite samples. (1st February 2020) - Elfers, Bo-Magnus; Sprung, Peter; Messling, Nils; Münker, Carsten
Abstract: The stepwise acid digestion of primitive chondritic meteorites allows the identification of nucleosynthetic isotope anomalies that are otherwise hidden on the bulk rock scale. Here, we present for the first time combined isotope data for acid leachates, residues, and bulk rock aliquots of several primitive chondrites for the geo- and cosmochemically similar elements Zr and Hf. Our analyses reveal significant Zr and Hf isotope anomalies that (i) are complementary between acid leachates and residues and (ii) well-correlated with each other. The observed Zr and Hf anomalies strongly suggest variable contributions of common s-process carrier phases to the different leachates and residues. Ratios of r- (and p-process) Zr and Hf isotopes appear to be uniform in leachates and residues. In contrast to the well-correlated anomalies found in our leaching experiments, nucleosynthetic Zr and Hf isotope signatures seem to be decoupled on the bulk rock scale. This contrast may result from the heterogeneous distribution of neutron-rich Zr material devoid Hf, or alternatively be caused by the presence of anomalous CAI material which overprinted s-process deficits that were initially correlated. In contrast to a previous study, we find no direct evidence for the presence of a third isotopically distinct nucleosynthetic Zr component.